2001
DOI: 10.1128/jvi.75.23.11811-11820.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Shrimp White Spot Bacilliform Virus

Abstract: We report the first complete genome sequence of a marine invertebrate virus. White spot bacilliform virus (WSBV; or white spot syndrome virus) is a major shrimp pathogen with a high mortality rate and a wide host range. Its double-stranded circular DNA genome of 305,107 bp contains 181 open reading frames (ORFs). Nine homologous regions containing 47 repeated minifragments that include direct repeats, atypical inverted repeat sequences, and imperfect palindromes were identified. This is the largest animal viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
353
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 512 publications
(368 citation statements)
references
References 59 publications
4
353
0
11
Order By: Relevance
“…Especially in infectious virus diseases, a lot of pathogenic viruses were identified from freshwater and marine culture animals [103], and the complete genomes of several viruses, such as grass carp hemorrhage virus (GCHV) [104], shrimp white spot syndrome virus (WSSV) [105], mandarin fish infectious spleen and kidney necrosis iridovirus (ISKNV) [106], and flounder lymphocystis disease virus isolated in China (LCDV-C) [107], were sequenced in China. Moreover, their structure proteins were characterized [108][109][110][111], and some of them were functionally analyzed [112,113].…”
Section: Disease Resistance Trait and Candidate Disease Resistance-rementioning
confidence: 99%
“…Especially in infectious virus diseases, a lot of pathogenic viruses were identified from freshwater and marine culture animals [103], and the complete genomes of several viruses, such as grass carp hemorrhage virus (GCHV) [104], shrimp white spot syndrome virus (WSSV) [105], mandarin fish infectious spleen and kidney necrosis iridovirus (ISKNV) [106], and flounder lymphocystis disease virus isolated in China (LCDV-C) [107], were sequenced in China. Moreover, their structure proteins were characterized [108][109][110][111], and some of them were functionally analyzed [112,113].…”
Section: Disease Resistance Trait and Candidate Disease Resistance-rementioning
confidence: 99%
“…1995). WSSV is an enveloped virus with a large, double-stranded, circular DNA genome (∼300 kb) containing approximately 180 putative open reading frames (ORFs), most of which have no homology with any known genes or proteins in public databases Wongteerasupaya et al 1995;Wang et al 1995;Chang et al 1996;Chen et al 1997;Yang et al 2001). Proper husbandry and management of farms with the application of immunostimulants, probiotics and bioremediators can save the industry from the onslaught of diseases to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies indicated that there is also little difference in virulence between various WSSV isolates, although direct comparisons were not made (Wang et al, 1999;Lan et al, 2002). After the complete sequencing of three different WSSV isolates originating from Taiwan (WSSV-TW; Wang et al, 1995), China (WSSV-CN; Yang et al, 2001) and Thailand (WSSV-TH;van Hulten et al, 2001), the major variable loci in the WSSV genome were mapped by alignment of these sequences (Marks et al, 2004). Roughly, the variable loci can be divided into deletions, variable numbers of tandem repeats (VNTRs), single nucleotide indels and single nucleotide polymorphisms (SNPs).…”
Section: Introductionmentioning
confidence: 99%
“…The circular dsDNA genome of WSSV has a size of around 300 kb and is one of the largest animal virus genomes that has been entirely sequenced (van Hulten et al, 2001;Yang et al, 2001). Only 6 % of the putative 184 ORFs encoded by the viral genome have homologues in public databases, mainly representing genes encoding enzymes for nucleotide metabolism, DNA replication and protein modification (van Hulten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%